ANALISIS PUBLIKASI DAN LAPORAN KEUANGAN LAZISMU BERDASARKAN PSAK NO. 45 (STUDI KASUS LAZISMU MENTENG JAKARTA PUSAT) - Haryanto, Agung; Yeni, Fatma (Jurnal Ekonomi Islam, 2019)
Cheng, Q., Y. Cho, and H. Yang. Financial reporting changes and the internal information environment: Evidence from SFAS 142. Review of Accounting Studies 23: 347-83. 2018. Cho, Y. J., Segment disclosure transparency and internal capital market efficiency: Evidence from SFAS No. 131, Journal of Accounting Research 53: 669-723. 2015, Dewi, N F, Azam dan Yusoff.,Factors influencing the information quality of local government financial statements and financial accountability. Management Science Letters. 2019. E, Adewale dan M. Babajide., corporate governance and quality of financial reporting; Nigeria perspective. International Journal of Education Humanities and Social Science. 2019. Graham, J., M. Hanlon, dan T. Shevlin, Real effects of accounting rules: Evidence from multinational firms? investment location and profit repatriation decisions, Journal of Accounting Research 49: 137-18. 2011 Harahap, Sofyan Syahri. A Statement of Basic Accounting Theory (ASOBAT). Penerbit PT Raja Grafindo Persada. Jakarta. 2007 Heitzman, Shane, dan Huang., Internal Information Quality and the Sensitivity of Investment to Market Prices and Accounting Profits. 2018. Martani, Dwi, et al., Akuntansi Keuangan Menengah Berbasis PSAK. Jakarta: Salemba Empat. 2012 Safkur, dkk., The Effect of Quality Financial Reporting on Good Governance: 2146-4138. 2019 Sanchez dan Ferrero.,Corporate Reputation As A Consequence Of Financial Reporting Quality. International Management & Economics Frontiers. 2016 Shroff, N., Corporate investment and changes in GAAP, Review of Accounting Studies 22: 1-63. 2017  Suwardjono. Teori Akuntansi: Perekayasaan Pelaporan Keuangan. Yogyakarta: BPFEYogyakarta. 2006. Wang, Cao dan Ye. Mandatory Corporate Social Responsibility (CSR) Reporting and Financial Reporting Quality: Evidence from a Quasi-Natural Experiment. 2016